Stomatal conductance of maize under water and nitrogen deficits - Medici, Leonardo Oliveira; Azevedo, Ricardo Antunes; Canellas, Luciano Pasqualoto; Machado, Altair Toledo; Pimentel, Carlos (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the effect of drought and nitrogen (N) stresses on stomatal conductance of three maize cultivars grown in the field. The stomatal conductance of Sol da Manhã variety (BRS 4157) and Pioneer 6875 hybrid, under drought and high N, was lower than under drought and low N, which indicates drought tolerance, since these cultivars did not exhibit reduction in grain yield by drought, as observed for Amarelão variety, which flowered under more severe drought. 'Sol da Manhã' exhibited shorter anthesis-silking interval under high N than under low N, an additional indication of tolerance.